Time-course effects of exercise intervention on executive function in adolescents with obesity - Hu, Lingling; Shen, Qiqi; Yin, Hengchan; Cui, Lei (Frontiers in Psychology, 2024)
Objective: This study was to investigate the developmental characteristics of executive function (EF) in obese adolescents and the time-course effects of a 14-week exercise intervention combining aerobic exercise and resistance training on EF in this population. Methods: The experimental group of 28 obese junior high school students participated in the exercise intervention combining aerobic exercise and resistance training, while the control group of 24 healthy weight junior high school students engaged in the regular recess exercise. EF, including inhibition, working memory, and cognitive flexibility, was assessed one week prior to the exercise intervention and at 12 and 14 weeks post-intervention. Changes in EF sub-functions in both groups at different time points during the exercise intervention were analyzed. Results: The findings revealed that obese junior high school students exhibited lower levels of inhibition (p=0.003, Cohen's d=0.848) and cognitive flexibility (p=0.013, Cohen's d=0.706) compared to their healthy weight peers. The exercise intervention combining aerobic exercise and resistance training led to significant improvements in EF among obese junior high school students, with inhibition (p<0.01, Cohen's d=0.713; p=0.003, Cohen's d=0.683) and cognitive flexibility (p=0.001, Cohen's d=0.797; p<0.01, Cohen's d=0.890) showing significant improvement at 12 and 14 weeks post-intervention, and working memory demonstrating significant improvement at 14 weeks (p=0.004, Cohen's d=0.710). No significant differences were observed in EF over time in healthy weight junior high school students. Conclusion, Obese adolescents had impaired EF, as evidenced by low levels of the inhibition and cognitive flexibility compared to healthy weight adolescents. The exercise intervention combining aerobic exercise and resistance training had a positive effect on EF of obese adolescents. The time-course effects of the intervention on improvements in inhibition, working memory, and cognitive flexibility varied with intervention duration in obese adolescents, with significant changes in inhibition and cognitive flexibility observed at 12 weeks and significant changes in working memory at 14 weeks.